Outward Mobility of Saudi Students: An Overview - Ahmed, Manail Anis (International Higher Education, 2015)
Since 1927, the Kingdom of Saudi Arabia has continuously committed substantial sums of money—and corresponding amounts of energy and effort—into educating its citizens abroad. From the first six students to be sent to Cairo to acquire higher education, to the currently almost 200,000 students studying a wide variety of disciplines across the world, this phenomenon has come a long way indeed. In addition, due to a booming economy and high per capita income, many Saudi families can privately afford to send their wards of university age to study abroad. This article provides a brief survey of the latest figures released by the Saudi Ministry of (formerly Higher) Education with regard to Saudi students’ outward mobility, reviewing trends for scholarship and privately-funded students by destination country, field of study, and academic level. It also briefly examines the inclusion of large numbers of Saudi female students in this cohort, and the accompanying social and cultural implications of this trend on the Kingdom of Saudi Arabia.